2000
DOI: 10.1046/j.1365-2672.2000.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure, production characteristics and fungal antagonism of tensin - a new antifungal cyclic lipopeptide from Pseudomonas fluorescens strain 96.578

Abstract: Aim: To study the antagonistic activity by Pseudomonas¯uorescens strain 96.578 on the plant pathogenic fungus Rhizoctonia solani. Methods and Results: Strain 96.578 produced a new cyclic lipopeptide, tensin. High tensin production per cell was detected in liquid media with glucose, mannitol or glutamate as growth substrate while fructose, sucrose and asparagine supported low production. Tensin production was nearly constant in media with different initial C levels, while low initial N contents reduced producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 22 publications
5
92
0
1
Order By: Relevance
“…When P. fluorescens strains 96.578 and DSS73 were added to bulk soil, the CFU counts were nearly constant over a 1-week period, as shown in Fig. 3B and C. Unlike viscosinamide, the tensin and amphisin compounds produced by these strains show only limited binding to the producing cells (17), and washing the inocula before adding them to the soil therefore results in very low initial CLP concentrations. The calculated initial tensin concentration was thus 8 ng g of dry soil Ϫ1 on day zero, which was below the detection limit in the soil (ϳ60 ng g of dry soil Ϫ1 ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…When P. fluorescens strains 96.578 and DSS73 were added to bulk soil, the CFU counts were nearly constant over a 1-week period, as shown in Fig. 3B and C. Unlike viscosinamide, the tensin and amphisin compounds produced by these strains show only limited binding to the producing cells (17), and washing the inocula before adding them to the soil therefore results in very low initial CLP concentrations. The calculated initial tensin concentration was thus 8 ng g of dry soil Ϫ1 on day zero, which was below the detection limit in the soil (ϳ60 ng g of dry soil Ϫ1 ).…”
Section: Resultsmentioning
confidence: 91%
“…All three P. fluorescens strains, DR54, 96.578, and DSS73, were initially selected as being capable of antagonizing P. ultimum and R. solani on plates and during the early seed germination and root development of sugar beets (13,15,16,17,23,24). When looking for antibiotics involved in this antagonistic activity in vitro, it has been shown that purified CLPs from these three strains have inhibitory activity toward both P. ultimum and R. solani (15,16,17). A prerequisite for CLP production to be involved in fungal inhibition in soils is that the P. fluorescens strains be active and produce the CLP compounds after sugar beet seeds are coated with the bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the capacity to synthesize toxic cyclic lipopeptides (Andersen et al, 2003;Koch et al, 2002;Thrane et al, 2000) they are used as effective biological control agents (Sorensen et al, 2001). Many authors have reported that these purified lipopeptides show an antagonistic activity against certain fungi pathogenic on sugar beet roots such as Rhizoctonia solani (Andersen et al, 2003;Nielsen et al, 2000Nielsen et al, , 2002, Aphanomyces cochlioides (Raaijmakers et al, 2010;Sorensen et al, 2001), Pythium ultimum and Pythium debarianum (Andersen et al, 2003;Gorlach-Lira & Stefaniak, 2009;Lee et al, 2000;Nielsen et al, 2000;Thrane et al, 2000). This suggests that bacteria producing lipopeptides could have a potential role in the biocontrol of fungal diseases, which was approved in both laboratory and field trials (Thrane et al, , 2001.…”
mentioning
confidence: 99%